Add-on sight for the Hailstorm product family - Koivusalo, Lauri (My University, 2024)
This bachelor’s thesis was made for OY Forcit Ab and the overarching task was to come up with a new sight concept for the Hailstorm product family. A client survey was conducted to clarify the requirements and wishes for the new sight and its features. To accompany the client survey, benchmarking of existing sight technologies was conducted, and the technologies used are outlined. A literature review into product development methodologies and techniques was also done, concentrating on trends for small and medium sized enterprises and agile product development. After analyzing the information from market research and the client survey, I designed a new mounting system for a removable sight for Hailstorm devices. The new sighting system consists of two independent sights, a flip up sight built into the shell of the device and a detachable sight with a mount, able to be slid over the flip up sight onto a rail. The goal of the new sight is to improve user friendliness and accuracy while being able to be operated in varying environments.
Keywords: Product development, sighting device